Structures and processes of care in ambulatory oncology settings and nurse-reported exposure to chemotherapy. Issue 9 (16th August 2011) - Friese, Christopher R; Himes-Ferris, Laurel; Frasier, Megan N; McCullagh, Marjorie C; Griggs, Jennifer J
Abstract : Purpose: Oncology nurses in ambulatory settings are at increased risk for unintentional chemotherapy exposure due to the large volumes of agents delivered and the absence of regulatory enforcement. Given the limited data regarding the correlates of exposure, the authors sought to identify the relationship between the organisational structures and processes of care in ambulatory oncology settings associated with increased risk of unintentional chemotherapy. Methods: Between April 2010 and June 2010, a state-wide sample of oncology nurses were surveyed who reported their employment outside of hospital inpatient units (n=1339). The survey examined the likelihood of self-reported exposure to chemotherapy as a function of perceived quality of the practice environment, nursing workload, and seven ambulatory chemotherapy administration safety standards. Results: The response rate was 30.4%, with minimal demographic differences observed between respondents and non-respondents. The overall rate of exposure to the skin or eyes in the past year was 16.9%. In multivariable logistic regression models that controlled for demographic characteristics and clustering of nurses in practices, the likelihood of exposure decreased when nurses reported adequate staffing and resources (OR 0.35, 95% CI 0.17 to 0.73; p = 0.001), and when nurses reported that chemotherapy doses were verified by two nurses frequently or very frequently (OR 0.17, 95% CI 0.05 to 0.59; p=0.001). Conclusions: Oncology nurses in the ambulatory setting report substantial unintentional skin and eye exposure to chemotherapy. Ensuring adequate staffing and resources and adherence to recognised practice standards may protect oncology nurses from harm.